Keeping the plan ready through awareness, testing and maintenance - Dengler, Natalie M. (Henry Stewart Talks, 2011)
Business Continuity Management (BCM), Components of business resiliency program, Awareness program, Awareness material, Using existing material, Business continuity risks, Testing program, Role of BCM coordinator, Types of tests, Table top-scenario based test, Full physical test, Maintenance program, Quantitative assessment, Self assessment scorecard, Keeping the plan ready